2008
DOI: 10.1002/bit.22147
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen/deuterium exchange study of subtilisin Carlsberg during prolonged exposure to organic solvents

Abstract: It has been previously reported that prolonged exposure of an enzyme to organic solvents leads to substantial decrease of activity. This effect was found to be unrelated to the catalysts' structure or their possible aggregation in organic solvents, and up to the present day the cause for activity loss remains unclear. In the present work, the structural dynamics of the serine protease subtilisin Carlsberg (SC) have been investigated during prolonged exposure to two organic solvents by following hydrogen/deuter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The partial inactivation mechanism is not clearly understood for esterases but inactivation is independent of physicochemical properties of the solvent, hydration state and temperature (Castillo et al, 2006). A decrease in activity of the serine protease subtilisin Carlsberg in solvents was thought to involve a diminishing ability to stabilize the transition state or minor structural disorders, such as reorientation of the oxyanion hole, that force substrates to adopt a less catalytically active conformation (Fasoli et al, 2009). The fact that the different feruloyl esterases lost activity at different rates, and in some cases increased activity suggests that the effect is not based on a change in solubility of the substrate in the solvent, but in individual and different changes in the active site of each esterase.…”
Section: Effect Of Solvent On Activity Against Methyl P-hydroxycinnammentioning
confidence: 98%
“…The partial inactivation mechanism is not clearly understood for esterases but inactivation is independent of physicochemical properties of the solvent, hydration state and temperature (Castillo et al, 2006). A decrease in activity of the serine protease subtilisin Carlsberg in solvents was thought to involve a diminishing ability to stabilize the transition state or minor structural disorders, such as reorientation of the oxyanion hole, that force substrates to adopt a less catalytically active conformation (Fasoli et al, 2009). The fact that the different feruloyl esterases lost activity at different rates, and in some cases increased activity suggests that the effect is not based on a change in solubility of the substrate in the solvent, but in individual and different changes in the active site of each esterase.…”
Section: Effect Of Solvent On Activity Against Methyl P-hydroxycinnammentioning
confidence: 98%
“…For instance, Trodler et al [17] reported that the flexibility of lipase B from Candida Antarctica (CALB) decreases with increasing log P values of organic solvents. Fasoli et al [21] also revealed that the flexibility of subtilisin from Bacillus licheniformis in octane (log P = 4.183) was lower than in acetonitrile (log P =´0.334). As discussing the flexibility of the enzyme, it was worthily noted that enyzme flexibility was usually determined from MD simulations and it is measured by the relative calculated B-factors [22].…”
Section: Effect Of Log P Value Of Organic Solventmentioning
confidence: 99%
“…Through MD simulation, acetonitrile molecules were found to penetrate into the active site of lipase, leading to structure variation of the active site and therefore the drop in the enzymatic activity in acetonitrile aqueous solution [38]; acetone, acetonitrile, and 1,4-dioxane could bind to the active site of subtilis and disturb its structure [21,34]. Gupta et al [39] observed that the activity of polyphenol oxidase and trypsin reduced to different extents by 50% of tetrahydrofuran, dioxane, acetone, and acetonitrile.…”
Section: Effect Of the Functional Groups Of Organic Solventmentioning
confidence: 99%
“…Although those results were inconclusive as to pinpointing the mechanistic reason for this observed decrease of initial enzyme activity, two different components were observed in the EPR spectra whose percentages changed during the incubation period, giving the first indication that perhaps the observed activity loss was due to an effect localized at the active site [9]. Furthermore, two recent studies shed additional light to this phenomenon: the first study looked at the enzyme dynamics by measuring the H/D exchange by NMR, and showed that globally, the enzyme becomes more rigid upon storage in acetonitrile (ACN) and 1,4-dioxane [11]. As previously observed the enantioselectivity remained constant, which is an indication that the active-site structure remained intact.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly however, was the fact that there was no correlation between enzyme flexibility and activity. The most active preparation (PEG-SC) was less flexible than the less active lyophilized preparation, and both preparations were more flexible in ACN than in 1,4-dioxane (the enzyme is more active in the second solvent) [11]. These results suggested to us that decreased global flexibility might not be the only cause of the observed loss of activity upon prolonged storage in organic media, and that other factors must be involved.…”
Section: Introductionmentioning
confidence: 99%